Accelerating widespread adoption of direct air capture based on system perspective: Thermodynamic limits, geographical deployment, and clean energy integration - Li,C; Deng,S; Cao,XE; Li,S (Renewable and Sustainable Energy Reviews, 2026)
Direct Air Capture (DAC) is a critical negative emission technology essential to achieve the global climate targets. However, its widespread adoption is hindered by a multitude of technical, economic, deployment, and sustainability challenges. The purpose of this review is to bridge this critical gap by deconstructing the challenges and opportunities for DAC through a novel, three-tiered analytical framework. Basically, the fundamental challenge of DAC lies in the high energy consumption and low exergy efficiency associated with CO2 enrichment from its low atmospheric concentration. Analysis suggests that the thermodynamic limits of different DAC pathways, which dictate their theoretical energy consumption, are the primary determinants of their technological maturity and potential for large-scale development. From the perspective of geographical deployment, the idealized notion of placing DAC facilities anywhere is unfeasible due to practical, location-specific constraints. Combining large-scale centralized hubs with agile distributed units is a critical enabler for achieving diversified and efficient deployment. Furthermore, as the environmental benefits of DAC are critically dependent on the availability of clean energy, effective integration with the energy system is paramount. The argument of this review is that DAC, when combined with CO2 utilization and storage and powered by clean energy, may hold distinct advantages over Bioenergy with Carbon Capture and Storage (BECCS) in terms of theoretical removal potential and resource sustainability, presenting a fundamental opportunity for DAC to become a true negative carbon solution. By providing such a holistic synthesis, our work establishes a strategic roadmap for prioritizing research, investment, and policy, transforming the discourse from isolated technical problems to a cohesive system-engineering challenge.